PELATIHAN PEMBUATAN DAN PENGEMBANGAN BAHAN AJAR DI TAMAN PENDIDIKAN AL-QUR’AN DESA SEMPU - Muhamad Imam Mutamaqin; Ahmad Ibnu Mubarok; Muhammad Reza Syahida; Hilya Nur Lidia Putri; Nur Kholisoh (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
The development of Islamic religious knowledge learning facilities and strategies for making and developing teaching materials for each religious line in Sempu Village, Ngancar District, Kediri Regency are reviewed. Guidelines on religious knowledge are something that is greatly needed by the Sempu Village community, which is still considered to have minimal religious knowledge. This study uses a participatory action research (PAR) approach method which is one of the qualitative action research. Researchers found that several TPQ in Sempu Village only studied how to read and write the Qur'an with learning facilities that were not yet systematic, furthermore, other insights about religion were still not fulfilled, so that religious practices in everyday life were still lacking. Thus, team created a teaching material program that briefly and concisely discussed the challenges of Islamic jurisprudence, morals, and how to read the Qur'an properly and correctly. These guidebooks are distributed to every TPQ in Sempu Village to be used as a guide for the male/female teachers in teaching, with the hope that these guidebooks can provide benefits for the TPQ children and the Sempu Village community.